Immunomodulatory effects of G-CSF in cancer: Therapeutic implications. (April 2021) - Mouchemore, Kellie A.; Anderson, Robin L.
Abstract: Numerous preclinical studies have reported a pro-tumour role for granulocyte colony-stimulating factor (G-CSF) that is predominantly mediated by neutrophils and MDSCs, the major G-CSF receptor expressing populations. In the presence of G-CSF (either tumour-derived or exogenous) these myeloid populations commonly exhibit a T cell suppressive phenotype. However, the direct effects of this cytokine on other immune lineages, such as T and NK cells, are not as well established. Herein we discuss the most recent data relating to the effect of G-CSF on the major immune populations, exclusively in the context of cancer. Recent publications have drawn attention to the other tumour-promoting effects of G-CSF on myeloid cells, including NETosis, promotion of cancer stemness and skewed differentiation of bone marrow progenitors towards myelopoiesis. Although G-CSF is safely and commonly used as a supportive therapy to prevent or treat chemotherapy-associated neutropenia in cancer patients, we also discuss the potential impacts of G-CSF on other anti-cancer treatments. Importantly, considerations for immune checkpoint blockade are highlighted, as many publications report a T cell suppressive effect of G-CSF that may diminish the effectiveness of this immunotherapy.